PAHIS: Pacific animal health information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Alexandre Fediaevsky reports on the Pacific Animal Health Information System (PAHIS), a database and decision support system issued on CD-ROM for veterinary officers in the region.